Chemical-resistant transparent polyamide, preparation method thereof and polyamide injection molded part
By treating alicyclic transparent nylon and long carbon chain nylon under vacuum and high temperature conditions, semi-block copolymers were prepared, which solved the problem of insufficient chemical resistance of traditional transparent polyamides and achieved a polyamide material with high transmittance and good chemical resistance.
Patent Information
- Application Number
- CN202411955157.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-15
AI Technical Summary
The chemical resistance of traditional transparent polyamides is poor, especially poor resistance to alcohol solvents, which leads to whitening and fogging in some applications, limiting its application range.
Chemically resistant transparent polyamide was prepared by mixing and melting alicyclic transparent nylon, long carbon chain nylon and additives under protective atmosphere and sealed conditions, and stirring reactions under vacuum conditions of 260°C to 290°C. This method allows the nylon residual carboxyl and amino group to condense and polymerize to form semiblock copolymers, improving the chemical resistance of the material.
The prepared chemically resistant transparent polyamide not only has excellent transmittance, but also significantly improves the tolerance to alcohol solvents, reduces the transmittance and haze reduction after soaking in alcohol solvents, and has good mechanical and thermal properties.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and in particular to a chemically resistant transparent polyamide and a preparation method thereof, and a polyamide injection molded part. Background Art
[0002] Polyamide, also known as nylon, is a general term for polymers containing amide groups in the repeating units of the macromolecular main chain. It can be prepared by the ring-opening polymerization of lactams or by the condensation polymerization of diamines and dibasic acids.
[0003] Transparent polyamide is a type of polyamide, and its aggregated state is amorphous or microcrystalline, with excellent transparency. Compared with other transparent materials, its transmittance is better than polycarbonate (PC), its stress cracking resistance is better than polymethyl methacrylate (PMMA), and its density is much lower than traditional glass. Therefore, it is widely used in glasses, lighting, electronic appliances and other fields.
[0004] Traditional transparent polyamide usually has an amorphous structure, so that when light passes through the material, it will not be strongly scattered due to the difference in refractive index between the crystalline area and the non-crystalline area, so that the material has good transparency; however, traditional transparent nylon has poor chemical resistance, especially poor tolerance to alcohol solvents such as ethanol and isopropanol. After immersion, it will turn white and foggy, which limits the application of transparent polyamide.
[0005] Therefore, conventional transparent polyamides still need to be further improved. Summary of the invention
[0006] Based on this, one or more embodiments of the present application provide a chemically resistant transparent polyamide with excellent chemical resistance and high transmittance, a preparation method thereof, and corresponding polyamide injection molded parts.
[0007] According to the first aspect of the present application, a method for preparing a chemically resistant transparent polyamide is provided, comprising the following steps:
[0008] In a protective atmosphere and sealed conditions, alicyclic transparent nylon, long carbon chain nylon and an additive are mixed and melted to obtain a mixture;
[0009] The mixture is stirred and reacted at 260° C. to 290° C. under vacuum conditions for 1 hour to 1.5 hours, and the chemically resistant transparent polyamide is obtained through extrusion, granulation and drying.
[0010] In some embodiments, the preparation method of the chemically resistant transparent polyamide satisfies at least one of the following conditions:
[0011] (1) The pressure value of the protective atmosphere is 0.1MPa~0.15MPa;
[0012] (2) The gas pressure of the vacuum condition is below -0.08 MPa;
[0013] (3) The drying temperature is 80°C to 90°C and the drying time is 8h to 12h;
[0014] (4) After the mixed melting and before the stirring reaction, the following step is further included: stirring the mixture at a speed of 25 r / min to 35 r / min for 25 min to 35 min.
[0015] In some embodiments, the auxiliary agent includes one or more of a UV absorber, a heat stabilizer, a lubricant, a release agent, and a nucleating agent;
[0016] Optionally, the ultraviolet absorber includes one or more of a dihydroxybenzene ring ultraviolet absorber, a benzophenone ultraviolet absorber, a benzotriazole ultraviolet absorber and a triazine ultraviolet absorber;
[0017] Optionally, the heat stabilizer includes one or more of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, phosphorous acid, sodium phosphite, tris(2,4-di-tert-butylphenyl)phosphite, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine and N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide;
[0018] Optionally, the lubricant includes one or more of a silicone lubricant, a fatty acid salt lubricant, a fatty acid amide lubricant, and a talc lubricant;
[0019] Optionally, the release agent includes one or more of a silicone release agent, a fatty acid salt release agent, a fatty acid amide release agent, and a talc release agent;
[0020] Optionally, the nucleating agent includes one or more of talc, montmorillonite, CAV102, NAV101 and P22.
[0021] In some embodiments, the preparation method of the chemically resistant transparent polyamide satisfies at least one of the following conditions:
[0022] (1) The alicyclic transparent nylon includes one or more of PAMACM12, PAPACM12 and MACM12 / PACM12 copolymer;
[0023] (2) The long carbon chain nylon includes one or more of PA1010, PA1012, PA1212 and PA12;
[0024] (3) The relative viscosity of the alicyclic transparent nylon in concentrated sulfuric acid is 1.9 to 2.2;
[0025] (4) The relative viscosity of the long carbon chain nylon in concentrated sulfuric acid is 2.2 to 2.4;
[0026] (5) The mass ratio of the alicyclic transparent nylon to the long carbon chain nylon is (1-7): (3-4);
[0027] (6) Based on the total mass of the alicyclic transparent nylon and the long carbon chain nylon, the amount of the additive added is 0.15wt%~3wt%.
[0028] In some embodiments, the method for preparing the alicyclic transparent nylon comprises the following steps:
[0029] The raw materials for preparing the alicyclic transparent nylon are mixed, and salt-forming reaction, prepolymerization reaction and polymerization reaction are carried out in sequence under closed conditions, and the alicyclic transparent nylon is obtained through extrusion, granulation and drying.
[0030] In some embodiments, the method for preparing the alicyclic transparent nylon satisfies at least one of the following characteristics:
[0031] (1) The raw materials for preparing the alicyclic transparent nylon include diamine monomers, diacid monomers, antioxidants and catalysts;
[0032] (2) The salt-forming reaction is carried out under the protective atmosphere conditions of 140° C. to 150° C. and 0.1 MPa to 0.15 MPa;
[0033] (3) The prepolymerization reaction is carried out at 270°C to 290°C and normal pressure, and the reaction time is 0.5h to 1h;
[0034] (4) The polymerization reaction is carried out at 270°C to 290°C, a gas pressure of less than -0.08 MPa, and a reaction time of 10 min to 20 min.
[0035] In some embodiments, the method for preparing the long carbon chain nylon comprises the following steps:
[0036] The raw materials for preparing the long carbon chain nylon are mixed, and salt-forming reaction, prepolymerization reaction and polymerization reaction are carried out in sequence under closed conditions, and the long carbon chain nylon is obtained through extrusion, granulation and drying.
[0037] In some embodiments, the method for preparing the long carbon chain nylon satisfies at least one of the following characteristics:
[0038] (1) The raw materials for preparing the long carbon chain nylon include diamine monomer, diacid monomer, antioxidant and catalyst;
[0039] (2) The salt-forming reaction is carried out under the protective atmosphere conditions of 90°C to 130°C and 0.1MPa to 0.15MPa;
[0040] (3) The prepolymerization reaction is carried out at 220°C to 250°C and normal pressure, and the reaction time is 0.5h to 1h;
[0041] (4) The polymerization reaction is carried out at 220°C to 250°C, a gas pressure of less than -0.08 MPa, and a reaction time of 10 min to 20 min.
[0042] According to a second aspect of the present application, a chemical-resistant transparent polyamide is provided, which is prepared by using the above-mentioned method for preparing the chemical-resistant transparent polyamide.
[0043] According to a third aspect of the present application, a polyamide injection molded part is provided, comprising the above-mentioned chemically resistant transparent polyamide.
[0044] Compared with the traditional technology, this application has the following beneficial effects:
[0045] The present application controls the reaction temperature within a specific range so that both the alicyclic transparent nylon and the long carbon chain nylon are in a viscous flow state and can flow freely, and provides activation energy for the reaction to increase the probability of collision between molecules; further, the reaction is carried out at high temperature and vacuum for a specific time to condense and polymerize the residual carboxyl and amino groups of the nylon to form a semi-block copolymer. The performance of the polyamide obtained in this way is between that of a random copolymer and a block copolymer, and has good chemical resistance, mechanical properties, thermal properties and transmittance. DETAILED DESCRIPTION
[0046] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.
[0048] In the present application, "plurality", "multiple", "multiple times", "multiples", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0049] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.
[0050] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0051] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1-10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.
[0052] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0053] In the present application, %(w / w) and wt% both refer to weight percentage, %(v / v) refers to volume percentage, and %(w / v) refers to mass volume percentage.
[0054] In a first aspect of the present application, a method for preparing a chemically resistant transparent polyamide is provided, including S10 and S30.
[0055] S10: Mixing and melting alicyclic transparent nylon, long carbon chain nylon and an additive in a protective atmosphere and under a closed condition to obtain a mixture;
[0056] S30: The mixture is stirred and reacted at 260° C. to 290° C. under vacuum conditions for 1 h to 1.5 h, and chemically resistant transparent polyamide is obtained through extrusion, granulation and drying.
[0057] The present application controls the reaction temperature within a specific range so that both the alicyclic transparent nylon and the long carbon chain nylon are in a viscous flow state and can flow freely, and provides activation energy for the reaction to increase the probability of collision between molecules; the reaction is carried out at high temperature and under vacuum for a specific time so that the residual carboxyl groups and amino groups of the alicyclic transparent nylon and the long carbon chain nylon are further condensed and polymerized to form a semi-block copolymer. The performance of the polyamide obtained in this way is between that of the random copolymer and the block copolymer, and has good chemical resistance, mechanical properties, thermal properties and transmittance.
[0058] In some embodiments, the pressure value of the protective atmosphere in S10 is 0.1 MPa~0.15 MPa.
[0059] In some embodiments, the protective atmosphere includes nitrogen.
[0060] As an example, the pressure value of the protective atmosphere in S10 may be 0.1 MPa, 0.11 MPa, 0.12 MPa, 0.13 MPa, 0.14 MPa, 0.15 MPa, or any value within the range formed by any two of the above point values.
[0061] As an example, the heating temperature in S30 can be 260℃, 261℃, 262℃, 263℃, 264℃, 265℃, 266℃, 267℃, 268℃, 269℃, 270℃, 271℃, 272℃, 273℃, 274℃, 275℃, 276℃, 277℃, 278℃, 279℃, 280℃, 281℃, 282℃, 283℃, 284℃, 285℃, 286℃, 287℃, 288℃, 289℃, 290℃, or any value within the range formed by any two of the above point values.
[0062] Further, the heating temperature in S30 is 270°C to 290°C; further, the heating temperature in S10 is 280°C to 290°C.
[0063] Controlling the reaction temperature within the above range can make both the alicyclic transparent nylon and the long carbon chain nylon in a viscous flow state, so that the particles can flow freely, giving activation energy to the reaction and increasing the probability of collision between molecules.
[0064] In some embodiments, the gas pressure of the vacuum condition in S30 is below -0.08 MPa.
[0065] Vacuum conditions are conducive to timely extraction of small molecules generated by the reaction from the reaction system, shifting the reaction equilibrium in a direction that is favorable to polymerization, and increasing the reaction conversion rate and the molecular weight of the polymer.
[0066] As an example, the gas pressure under the vacuum condition may be -0.08 MPa, -0.09 MPa, -0.1 MPa, or any value within the range formed by any two of the above point values.
[0067] As an example, the stirring reaction time in S30 can be 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, or any value within the range formed by any two of the above point values.
[0068] Controlling the reaction time within the above-specified range enables the reaction to proceed sufficiently.
[0069] In some embodiments, the drying temperature in S30 is 80° C. to 90° C., and the drying time is 8 h to 12 h.
[0070] As an example, the drying temperature can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, or any value within the range formed by any two of the above values. The drying time can be 8h, 9h, 10h, 11h, 12h, or any value within the range formed by any two of the above values.
[0071] In some embodiments, after the mixing and melting and before the stirring reaction, S20 is further included:
[0072] S20: Stir the mixture at a speed of 25 r / min to 35 r / min for 25 min to 35 min.
[0073] By stirring the mixture, heat transfer can be made more uniform, the probability of collision between molecules can be increased, and the reaction efficiency can be improved.
[0074] As an example, the stirring speed in S20 can be 25 r / min, 26 r / min, 27 r / min, 28 r / min, 29 r / min, 30 r / min, 31 r / min, 32 r / min, 33 r / min, 34 r / min, 35 r / min, or any value within the range formed by any two of the above point values. Further, the stirring speed is 30 r / min.
[0075] As an example, the stirring time in S20 can be 25 min, 26 min, 27 min, 28 min, 29 min, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, or any value within the range formed by any two of the above point values. Further, the stirring time is 30 min.
[0076] In some embodiments, the auxiliary agent includes one or more of a UV absorber, a heat stabilizer, a lubricant, a mold release agent, and a nucleating agent.
[0077] In some embodiments, the additive is added in an amount of 0.15 wt % to 3 wt % based on the total mass of the alicyclic transparent nylon and the long carbon chain nylon.
[0078] As an example, the amount of the additive can be 0.15wt%, 0.16wt%, 0.17wt%, 0.18wt%, 0.19wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3wt%, or any value within the range of any two of the above point values. Further, the amount of the additive is 0.7wt% to 1.5wt%.
[0079] In some embodiments, the ultraviolet absorber includes one or more of a bishydroxybenzene ring type ultraviolet absorber, a benzophenone type ultraviolet absorber, a benzotriazole type ultraviolet absorber, and a triazine type ultraviolet absorber.
[0080] In some embodiments, based on the total mass of the alicyclic transparent nylon and the long carbon chain nylon, the added amount of the ultraviolet absorber is 0.1 wt% to 1.5 wt%; further, the added amount of the ultraviolet absorber is 0.5 wt% to 1 wt%.
[0081] In some embodiments, the thermal stabilizer includes one or more of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, phosphorous acid, sodium phosphite, tris(2,4-di-tert-butylphenyl)phosphite, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine (Irganox 1098), and N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide (RIASORB® SEED).
[0082] Further, the heat stabilizer includes one or more of Irganox 1098 and RIASORB® SEED.
[0083] In some embodiments, based on the total mass of the alicyclic transparent nylon and the long carbon chain nylon, the amount of the heat stabilizer added is 0.05 wt % to 0.5 wt %; further, the amount of the heat stabilizer added is 0.1 wt % to 0.2 wt %.
[0084] In some embodiments, the lubricant includes one or more of a silicone-based lubricant, a fatty acid salt-based lubricant, a fatty acid amide-based lubricant, and a talc-based lubricant.
[0085] In some embodiments, based on the total mass of the alicyclic transparent nylon and the long carbon chain nylon, the sum of the added amounts of the lubricant and the release agent is 0-0.5 wt %; further, the sum of the added amounts of the lubricant and the release agent is 0.1 wt %-0.2 wt %.
[0086] In some embodiments, the release agent includes one or more of a silicone-based release agent, a fatty acid salt-based release agent, a fatty acid amide-based release agent, and a talc-based release agent.
[0087] In some embodiments, the nucleating agent includes one or more of talc, montmorillonite, CAV102, NAV101, and P22.
[0088] Further, the nucleating agent includes CAV102.
[0089] In some embodiments, the amount of the nucleating agent added is 0-0.5 wt % based on the total weight of the alicyclic transparent nylon and the long carbon chain nylon. Further, the amount of the nucleating agent added is 0.1 wt %-0.2 wt %.
[0090] In some embodiments, the mass ratio of alicyclic transparent nylon to long carbon chain nylon is (1-7):(3-4).
[0091] As an example, the mass ratio of alicyclic transparent nylon to long carbon chain nylon can be 1:3, 2:3, 3:3, 4:3, 5:3, 6:3, 7:3, 1:4, 2:4, 3:4, 5:4, 6:4, 7:4, or any value within the range formed by any two of the above point values.
[0092] Furthermore, the mass ratio of alicyclic transparent nylon to long carbon chain nylon is (4~6):4.
[0093] In some embodiments, the method for preparing alicyclic transparent nylon comprises step a:
[0094] Step a: Mix the raw materials for preparing alicyclic transparent nylon, carry out salt-forming reaction, prepolymerization reaction and polymerization reaction in sequence under closed conditions, and obtain alicyclic transparent nylon through extrusion, granulation and drying.
[0095] In some embodiments, the raw materials for preparing alicyclic transparent nylon include a diamine monomer, a diacid monomer, an antioxidant and a catalyst.
[0096] In some embodiments, the diamine monomers for preparing alicyclic transparent nylon include one or more of 4,4'-diamino-dicyclohexylpropane (PACP), 4,4'-diamino-dicyclohexylmethane (PACM), and 4,4'-diamino-3,3'-dimethyl-dicyclohexylmethane bis(4-amino-3-methylcyclohexyl)methane (MACM).
[0097] In some embodiments, the diacid monomer for preparing the alicyclic transparent nylon includes a linear diacid having a carbon number greater than or equal to 6. Further, the diacid monomer for preparing the alicyclic transparent nylon includes one or more of adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecane dicarboxylic acid, and dodecanedioic acid.
[0098] In some embodiments, the antioxidant for preparing alicyclic transparent nylon includes one or more of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, phosphorous acid, sodium phosphite, tris(2,4-di-tert-butylphenyl)phosphite, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine (Irganox 1098) and N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide (RIASORB® SEED).
[0099] Further, antioxidants for preparing alicyclic transparent nylon include Irganox 1098 and RIASORB® SEED.
[0100] In some embodiments, based on the total weight of the diamine monomer and the diacid monomer, the amount of the antioxidant added is 0.05 wt % to 0.2 wt %; further, the amount of the antioxidant added is 0.1 wt % to 0.15 wt %.
[0101] In some embodiments, the catalyst for preparing alicyclic transparent nylon includes one or more of phosphoric acid, sodium phosphate, phosphorous acid, sodium phosphite, and sodium hypophosphite.
[0102] Furthermore, the catalyst for preparing alicyclic transparent nylon includes phosphorous acid and sodium phosphite.
[0103] In some embodiments, the amount of the catalyst added is 0.01 wt% to 0.1 wt% based on the total weight of the diamine monomer and the diacid monomer; further, the amount of the catalyst added is 0.01 wt% to 0.05 wt%.
[0104] In some embodiments, the raw materials for preparing alicyclic transparent nylon further include a molecular weight regulator.
[0105] In some embodiments, the molecular weight regulator includes one or more of phthalic acid, terephthalic acid, sebacic acid, dodecanedioic acid, hexamethylenediamine, decanediamine, PACM, and MACM.
[0106] In some embodiments, the amount of the molecular weight regulator added is 0-3 wt % based on the total weight of the diamine monomer and the diacid monomer; further, the amount of the molecular weight regulator added is 0.5 wt %-2 wt %.
[0107] In some embodiments, the cycloaliphatic transparent nylon includes one or more of PAMACM12, PAPACM12, and MACM12 / PACM12 copolymer.
[0108] In some embodiments, the relative viscosity of the alicyclic transparent nylon in concentrated sulfuric acid is 1.9 to 2.2. As an example, the relative viscosity of the alicyclic transparent nylon in concentrated sulfuric acid can be 1.9, 2, 2.1, 2.2, or any value within the range formed by any two of the above point values.
[0109] In some embodiments, the salt-forming reaction in step a is carried out under protective atmosphere conditions of 140° C. to 150° C. and 0.1 MPa to 0.15 MPa.
[0110] As an example, the temperature of the salt-forming reaction in step a can be 140°C, 141°C, 142°C, 143°C, 144°C, 145°C, 146°C, 147°C, 148°C, 149°C, 150°C, or any value within the range formed by any two of the above point values.
[0111] As an example, the pressure of the protective atmosphere in the salt-forming reaction in step a can be 0.1 MPa, 0.11 MPa, 0.12 MPa, 0.13 MPa, 0.14 MPa, 0.15 MPa, or any value within the range formed by any two of the above values. Further, the protective atmosphere includes nitrogen.
[0112] In some embodiments, after the salt-forming reaction in step a and before the prepolymerization reaction, the following step is included: depressurizing to normal pressure at a temperature of 210° C. to 220° C.
[0113] In some embodiments, the prepolymerization reaction in step a is carried out at 270° C. to 290° C. and normal pressure, and the reaction time is 0.5 h to 1 h.
[0114] As an example, the time of the prepolymerization reaction in step a can be 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1 h, or any value within the range formed by any two of the above point values.
[0115] In some embodiments, the polymerization reaction in step a is carried out at 270° C. to 290° C., a gas pressure of less than -0.08 MPa, and a reaction time of 10 min to 20 min.
[0116] As an example, the temperatures of the prepolymerization reaction and the polymerization reaction in step a can be independently 270°C, 271°C, 272°C, 273°C, 274°C, 275°C, 276°C, 277°C, 278°C, 279°C, 280°C, 281°C, 282°C, 283°C, 284°C, 285°C, 286°C, 287°C, 288°C, 289°C, 290°C, or any value within the range formed by any two of the above point values.
[0117] As an example, the gas pressure of the polymerization reaction in step a can be -0.08 MPa, -0.09 MPa, -0.1 MPa, or any value within the range formed by any two of the above point values.
[0118] As an example, the polymerization reaction time in step a can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, or any value within the range formed by any two of the above point values.
[0119] In some embodiments, the method for preparing long carbon chain nylon comprises step b:
[0120] Step b: Mix the raw materials for preparing long carbon chain nylon, carry out salt-forming reaction, prepolymerization reaction and polymerization reaction in sequence under closed conditions, and obtain long carbon chain nylon through extrusion, granulation and drying.
[0121] In some embodiments, the raw materials for preparing long carbon chain nylon include diamine monomers, diacid monomers, antioxidants and catalysts.
[0122] In some embodiments, the long carbon chain nylon is selected from long straight chain nylons having a carbon number between two adjacent amide bonds greater than or equal to ten.
[0123] In some embodiments, the long carbon chain nylon includes one or more of PA1010, PA1012, PA1212, and PA12.
[0124] In some embodiments, the relative viscosity of long carbon chain nylon in concentrated sulfuric acid is 2.2 to 2.4. As an example, the relative viscosity of long carbon chain nylon in concentrated sulfuric acid can be 1.9, 2, 2.1, 2.2, 2.3, 2.4, or any value within the range formed by any two of the above point values.
[0125] In some embodiments, the antioxidant for preparing long carbon chain nylon includes one or more of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, phosphorous acid, sodium phosphite, tris(2,4-di-tert-butylphenyl)phosphite, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine (Irganox 1098) and N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide (RIASORB® SEED).
[0126] Further, antioxidants for preparing long carbon chain nylon include Irganox 1098 and RIASORB® SEED.
[0127] In some embodiments, based on the total weight of the diamine monomer and the diacid monomer, the amount of the antioxidant added is 0.05 wt % to 0.2 wt %; further, the amount of the antioxidant added is 0.1 wt % to 0.15 wt %.
[0128] In some embodiments, the catalyst for preparing long carbon chain nylon includes one or more of phosphoric acid, sodium phosphate, phosphorous acid, sodium phosphite, and sodium hypophosphite.
[0129] Furthermore, the catalyst for preparing long carbon chain nylon includes phosphorous acid and sodium phosphite.
[0130] In some embodiments, the amount of the catalyst added is 0.01 wt% to 0.1 wt% based on the total weight of the diamine monomer and the diacid monomer; further, the amount of the catalyst added is 0.01 wt% to 0.05 wt%.
[0131] In some embodiments, the raw materials for preparing long carbon chain nylon further include a molecular weight regulator.
[0132] In some embodiments, the molecular weight regulator includes one or more of phthalic acid, terephthalic acid, sebacic acid, dodecanedioic acid, hexamethylenediamine, decanediamine, PACM, and MACM.
[0133] In some embodiments, the amount of the molecular weight regulator added is 0-3 wt % based on the total weight of the diamine monomer and the diacid monomer; further, the amount of the molecular weight regulator added is 0.5-2 wt %.
[0134] In some embodiments, the salt-forming reaction in step b is carried out under protective atmosphere conditions of 90° C. to 130° C. and 0.1 MPa to 0.15 MPa.
[0135] As an example, the temperature of the salt-forming reaction in step b can be 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, or any value within the range formed by any two of the above point values.
[0136] As an example, the pressure of the protective atmosphere in the salt-forming reaction in step b can be 0.1 MPa, 0.11 MPa, 0.12 MPa, 0.13 MPa, 0.14 MPa, 0.15 MPa, or any value within the range formed by any two of the above values. Further, the protective atmosphere includes nitrogen.
[0137] In some embodiments, after the salt-forming reaction in step b and before the prepolymerization reaction, the following step is included: depressurizing to normal pressure at a temperature of 210° C. to 220° C.
[0138] In some embodiments, the prepolymerization reaction in step b is carried out at 220° C. to 250° C. and normal pressure, and the reaction time is 0.5 h to 1 h.
[0139] As an example, the time of the prepolymerization reaction in step b can be 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1 h, or any value within the range formed by any two of the above point values.
[0140] In some embodiments, the polymerization reaction in step b is carried out at 220° C. to 250° C., a gas pressure of less than -0.08 MPa, and a reaction time of 10 min to 20 min.
[0141] As an example, the temperatures of the prepolymerization reaction and the polymerization reaction in step b can be independently 220°C, 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, or any value within the range formed by any two of the above point values.
[0142] As an example, the gas pressure of the polymerization reaction in step b can be -0.08 MPa, -0.09 MPa, -0.1 MPa, or any value within the range formed by any two of the above point values.
[0143] As an example, the polymerization reaction time in step b can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, or any value within the range formed by any two of the above point values.
[0144] The total transmittance of the 2 mm thick chemically resistant transparent polyamide prepared by the above method of the present application is not less than 87%; the decrease in transmittance and haze after immersion in ethanol for 48 hours does not exceed 5%; and the above chemically resistant transparent polyamide also has good mechanical properties and thermal properties.
[0145] The preparation method of the chemical-resistant transparent polyamide of the present application has the advantages of simple process and large-scale production.
[0146] The semi-block polymer prepared in the present application has a performance attenuation between copolymerization and blending, and its microcrystalline structure enables it to have good chemical resistance.
[0147] The preparation method of the present application can selectively add different additives as needed to obtain polyamides with different special properties.
[0148] In a second aspect of the present application, a chemical-resistant transparent polyamide is provided, which is prepared by the above-mentioned preparation method of chemical-resistant transparent polyamide.
[0149] In a third aspect of the present application, a method for preparing a polyamide injection molded part is provided, comprising the following steps:
[0150] The chemical-resistant transparent polyamide is injection molded to obtain a polyamide injection molded part.
[0151] In some embodiments, the injection molding temperature is 230°C to 280°C.
[0152] As an example, the injection molding temperature can be 230°C, 235°C, 240°C, 245°C, 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C, or any value within the range formed by any two of the above point values.
[0153] In a fourth aspect of the present application, a polyamide injection molded part is provided, which is prepared by the above-mentioned method for preparing a polyamide injection molded part; or,
[0154] Comprises the chemically resistant transparent polyamide described above.
[0155] The above-mentioned injection molded parts of the present application can be used in the fields of glasses, underwater connectors, keyboards, electronic cigarettes, etc.
[0156] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.
[0157] Example 1
[0158] (1) Synthesis of alicyclic transparent nylon: 11.78 kg of dodecanedioic acid, 11.92 kg of MACM, 23.7 g of 1098, 2.37 g of 50% phosphorous acid aqueous solution and 11.85 kg of deionized water were added to a 50 L high-pressure reactor. The air in the reactor was purged with nitrogen 15 times. After the purging was completed, 0.1 MPa of nitrogen was filled in for protection. The reactor was heated to 145 °C for salt formation reaction, and then vented to normal pressure at 220 °C. The temperature was raised to 280 °C for reaction for 0.5 h, and then vacuumed to -0.08 MPa for reaction for 20 min. After pressurized extrusion, the reactor was stretched and pelletized, and dried at 80 °C for 8 h to obtain PAMACM12 with a relative viscosity of 1.92.
[0159] (2) Synthesis of long carbon chain nylon: 11.68 kg of dodecanedioic acid, 8.67 kg of decanediamine, 20.36 g of 1098, 2.03 g of 50% phosphorous acid aqueous solution and 10.18 kg of deionized water were added to a 50 L high-pressure reactor. The air in the reactor was discharged by nitrogen replacement 15 times. After the replacement was completed, 0.1 MPa of nitrogen was filled in for protection. The reactor was heated to 110 °C for salt formation reaction, and then vented to normal pressure at 220 °C. The temperature was raised to 250 °C for reaction for 0.5 h, and then evacuated to -0.08 MPa for reaction for 20 min. After pressurized extrusion, the reactor was stretched and pelletized, and dried at 80 °C for 8 h to obtain PA1012 with a relative viscosity of 2.28.
[0160] (3) 12 kg of PAMACM12, 8 kg of PA1012, 40 g of CAV102 and 20 g of 1098 were fully mixed in a high-speed mixer and put into a 50 L closed reactor. The air in the reactor was emptied by nitrogen replacement 15 times, and 0.15 MPa of nitrogen was filled to maintain the pressure. The temperature was raised to 280 °C. After the polymer in the reactor was dissolved, it was stirred at a speed of 30 r / min for 30 min, and then vacuumed to -0.092 MPa. The reaction was carried out for 1 h under stirring, and then extruded and pelletized after pressurization. The reactor was dried at 80 °C for 8 h to obtain chemically resistant transparent polyamide.
[0161] Example 2
[0162] (1) Synthesis of alicyclic transparent nylon: 11.78 kg of dodecanedioic acid, 3.57 kg of MACM, 7.37 kg of PACM, 22.7 g of 1098, 2.27 g of 50% phosphorous acid aqueous solution and 11.36 kg of deionized water were added to a 50 L high-pressure reactor. The air in the reactor was purged with nitrogen 15 times. After the purging was completed, 0.1 MPa of nitrogen was filled in for protection. The reactor was heated to 145 °C for salt formation reaction, vented to normal pressure at 220 °C, heated to 280 °C for reaction for 0.5 h, and then evacuated to -0.08 MPa for reaction for 20 min. After pressure extrusion, the reactor was stretched and pelletized, and dried at 80 °C for 8 h to obtain a MACM12 / PACM12 copolymer with a relative viscosity of 2.06, wherein the molar ratio of PACM to MACM was 7:3.
[0163] (2) Synthesize long carbon chain nylon by referring to the method of Example 1.
[0164] (3) 10 kg of MACM12 / PACM12 copolymer, 10 kg of PA1012, 40 g of CAV102 and 20 g of 1098 were fully mixed in a high-speed mixer and put into a 50 L closed reactor. The air in the reactor was evacuated by nitrogen replacement 15 times, and 0.15 MPa of nitrogen was filled to maintain the pressure. The temperature was raised to 280 °C. After the polymer in the reactor was dissolved, it was stirred at a speed of 30 r / min for 30 min, and then evacuated to -0.092 MPa. The reaction was carried out under stirring for 1 h, and then extruded and pelletized after pressurization. The reactor was dried at 80 °C for 8 h to obtain chemically resistant transparent polyamide.
[0165] Example 3
[0166] The method is basically the same as Example 1, except that the gas pressure of the vacuum condition during the synthesis of polyamide is different; specifically, step (3) in Example 3 is as follows:
[0167] 12kg PAMACM12, 8kg PA1012, 40g CAV102 and 20g 1098 were fully mixed in a high-speed mixer and put into a 50L closed reactor. The air in the reactor was emptied by nitrogen replacement 15 times, and 0.15MPa nitrogen was filled to maintain the pressure. The temperature was raised to 280°C. After the polymer in the reactor was dissolved, it was stirred at a speed of 30r / min for 30min, and then vacuumed to a gas pressure of -0.05MPa. The reaction was carried out for 1h under stirring, and the reactor was extruded and pelletized after pressurization. The reactor was dried at 80°C for 8h to obtain chemically resistant transparent polyamide.
[0168] Example 4
[0169] The method is basically the same as Example 1, except that the ratio of alicyclic transparent nylon and long carbon chain nylon added in the synthesis of polyamide is different; specifically, step (3) in Example 4 is as follows:
[0170] 4kg PAMACM12, 8kg PA1012, 40g CAV102 and 20g 1098 were fully mixed in a high-speed mixer and put into a 50L closed reactor. The air in the reactor was emptied by nitrogen replacement 15 times, and 0.15MPa nitrogen was filled to maintain the pressure. The temperature was raised to 280°C. After the polymer in the reactor was dissolved, it was stirred at a speed of 30r / min for 30min, and then vacuumed to -0.092MPa, reacted for 1h under stirring, extruded and pelletized after pressurization, and dried at 80°C for 8h to obtain chemical-resistant transparent polyamide.
[0171] Comparative Example 1
[0172] PAMACM12 and PA1012 were synthesized according to the method described in Example 1, and PAMACM12 and PA1012 were blended at a mass ratio of 6:4, mixed and extruded by a twin-screw extruder at a temperature range of 260° C., pelletized and dried at 80° C. for 8 h to obtain polyamide.
[0173] Comparative Example 2
[0174] 11.78kg of dodecanedioic acid, 4.77kg of MACM, 5.2kg of decanediamine, 21.75g of 1098, 2.17g of 50% phosphorous acid aqueous solution and 10.87kg of deionized water were added into a 50L high-pressure reactor, and the air in the reactor was discharged by nitrogen replacement 15 times. After the replacement was completed, 0.1MPa of nitrogen was filled in for protection, and the reactor was heated to 145°C for salt-forming reaction, and the pressure was vented to normal pressure at 220°C, and the temperature was raised to 250°C for reaction for 0.5h, and then the pressure was evacuated to -0.092MPa for reaction for 1h. After pressurized extrusion, the reactor was stretched and pelletized, and dried at 80°C for 8h to obtain polyamide.
[0175] Comparative Example 3
[0176] 11.78kg of dodecanedioic acid, 7.63kg of MACM, 3.12kg of decanediamine, 22.53g of 1098, 2.25g of 50% phosphorous acid aqueous solution and 11.26kg of deionized water were added into a 50L high-pressure reactor, and the air in the reactor was discharged by nitrogen replacement 15 times. After the replacement was completed, 0.1MPa of nitrogen was filled in for protection, and the reactor was heated to 145°C for salt-forming reaction, and the pressure was vented to normal pressure at 220°C, and the temperature was raised to 260°C for reaction for 0.5h, and then the pressure was evacuated to -0.092MPa for reaction for 1h. After pressurized extrusion, the reactor was stretched and pelletized, and dried at 80°C for 8h to obtain polyamide.
[0177] Comparative Example 4
[0178] The method is basically the same as Example 1, except that vacuum is not applied during the synthesis of polyamide. Specifically, step (3) in Comparative Example 4 is as follows:
[0179] 12kg PAMACM12, 8kg PA1012, 40g CAV102 and 20g 1098 were fully mixed in a high-speed mixer and put into a 50L closed reactor. The air in the reactor was emptied by nitrogen replacement 15 times, and 0.15MPa nitrogen was filled to maintain the pressure. The temperature was raised to 280°C. After the polymer in the reactor was dissolved, it was stirred at a speed of 30r / min for 30min, reacted for 1h under stirring, extruded and pelletized after pressurization, and dried at 80°C for 8h to obtain polyamide.
[0180] Performance Testing
[0181] The relative viscosity was measured using an Ubbelohde viscometer in 96% concentrated sulfuric acid at a temperature of 25°C and a concentration of 0.01 g / mol.
[0182] The glass transition temperature (Tg), melting temperature (Tm) and melting enthalpy were measured by differential scanning calorimetry (DSC) with a heating and cooling rate of 10 K / min.
[0183] The transmittance and haze were measured using a haze meter, and the sample size was a 2 mm thick square plate.
[0184] The 2 mm thick square plate was immersed in anhydrous ethanol at 23°C for 48 hours and the transmittance and haze were measured again.
[0185] A dumbbell-shaped test bar with a size of 170 mm*10 mm*4 mm and a test bar with a size of 80 mm*10 mm*4 mm were obtained by injection molding at 250°C.
[0186] At 23°C, the tensile strength and elongation at break were tested on a dumbbell specimen of 170mm*10mm*4mm in accordance with ISO 527. The flexural strength and flexural modulus were tested on a test strip of 80mm*10mm*4mm in accordance with ISO 178. The notched cantilever beam impact strength was tested on a test strip of 80mm*10mm*4mm in accordance with ISO 180. The heat deformation temperature was tested at 1.8MPa with reference to ISO 75-2. The density was tested in accordance with ISO 1183.
[0187] The PAMACM12 prepared in Examples 1 to 4, Comparative Examples 1 to 4 and Example 1 were tested with reference to the above methods or test standards, and the results are shown in the following table.
[0188] Table 1
[0189]
[0190] In the above table, the Tm of Example 2 is "150 / 220", where 150°C corresponds to the melting temperature of the 1012 structural portion, and 220°C corresponds to the melting temperature of the MACM12 / PACM12 copolymer itself; similarly, the melting enthalpy "2.61 / 2.39" where 2.61 J / g corresponds to the melting enthalpy of the 1012 structural portion, and 2.39 J / g corresponds to the melting enthalpy of the MACM12 / PACM12 copolymer structural portion.
[0191] Table 2
[0192]
[0193] It can be seen from the above table that the polyamide prepared in Examples 1 to 4 has good mechanical properties, thermal properties, transmittance and haze, and still has good transmittance after being immersed in anhydrous ethanol, indicating that the polyamide prepared in this application has good chemical permeability.
[0194] Comparative Example 1 uses twin-screw extrusion to prepare polyamide. However, the vacuum treatment time of twin-screw extrusion is short and the length of the screw is limited, so a semi-block copolymer cannot be prepared. In addition, the residual end groups of PAMACM12 and PA1012 are not large, and the reactivity of amino and carboxyl groups is not high. Twin-screw extrusion cannot meet the reaction conditions. In the physical blend finally prepared, PA1012 still maintains good crystallization properties, resulting in reduced transmittance and increased haze. In addition, the compatibility of nylon itself will result in poor optical properties.
[0195] In Comparative Examples 2 and 3, the raw materials for preparing alicyclic transparent nylon and long carbon chain nylon are directly added into the reactor together, and finally a random copolymer is obtained; after copolymerization, the tensile strength and heat deformation temperature of the material are seriously reduced due to its random characteristics.
[0196] In Comparative Example 4, no vacuum was applied during the synthesis of the polyamide, and the elongation at break and notched Izod impact strength of the polyamide finally obtained were greatly reduced, the transmittance was reduced, and the haze was increased.
[0197] The copolymerization ratio of PA1012 in Comparative Example 3 is about 40%, and the copolymerization ratio of PA1012 in Comparative Example 2 is about 60%. Finally, the polyamide prepared in Comparative Example 2 has higher transmittance and lower haze after immersion in refined ethanol, but the tensile properties and heat deformation temperature are reduced; indicating that increasing the copolymerization ratio of PA1012 can further improve the chemical resistance of polyamide.
[0198] In Example 3, the gas pressure was evacuated to -0.05 MPa. Compared with Examples 1 and 2, the elongation at break of the prepared polyamide was reduced, the transmittance was slightly reduced, the haze was increased, and the melting enthalpy was significantly increased, indicating that the comprehensive performance of the polyamide prepared in Examples 1 and 2 was better.
[0199] In Example 4, the mass ratio of alicyclic transparent nylon to long carbon chain nylon is 1:2. Compared with Examples 1-2, the tensile strength, flexural strength and flexural modulus of the prepared polyamide are reduced, the heat deformation temperature is reduced, the haze is increased, and the melting enthalpy is significantly increased; indicating that the comprehensive performance of the polyamide prepared in Examples 1-2 is better.
[0200] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0201] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A method for preparing a chemically resistant transparent polyamide, characterized in that: The steps include: In a protective atmosphere and sealed conditions, alicyclic transparent nylon, long carbon chain nylon and an additive are mixed and melted to obtain a mixture; The mixture is stirred and reacted at 260° C. to 290° C. under vacuum conditions for 1 hour to 1.5 hours, and the chemically resistant transparent polyamide is obtained through extrusion, granulation and drying.
2. The method for preparing chemically resistant transparent polyamide according to claim 1, characterized in that: The preparation method of the chemically resistant transparent polyamide satisfies at least one of the following conditions: (1) The pressure value of the protective atmosphere is 0.1MPa~0.15MPa; (2) The gas pressure of the vacuum condition is below -0.08 MPa; (3) The drying temperature is 80°C to 90°C and the drying time is 8h to 12h; (4) After the mixed melting and before the stirring reaction, the following step is further included: stirring the mixture at a speed of 25 r / min to 35 r / min for 25 min to 35 min.
3. The method for preparing the chemically resistant transparent polyamide according to any one of claims 1 to 2, characterized in that: The auxiliary agent includes one or more of a UV absorber, a heat stabilizer, a lubricant, a release agent and a nucleating agent; Optionally, the ultraviolet absorber includes one or more of a dihydroxybenzene ring ultraviolet absorber, a benzophenone ultraviolet absorber, a benzotriazole ultraviolet absorber and a triazine ultraviolet absorber; Optionally, the heat stabilizer includes one or more of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, phosphorous acid, sodium phosphite, tris(2,4-di-tert-butylphenyl)phosphite, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine and N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide; Optionally, the lubricant includes one or more of a silicone lubricant, a fatty acid salt lubricant, a fatty acid amide lubricant, and a talc lubricant; Optionally, the release agent includes one or more of a silicone release agent, a fatty acid salt release agent, a fatty acid amide release agent and a talc release agent; Optionally, the nucleating agent includes one or more of talc, montmorillonite, CAV102, NAV101 and P22.
4. The method for preparing the chemically resistant transparent polyamide according to any one of claims 1 to 2, characterized in that: The preparation method of the chemically resistant transparent polyamide satisfies at least one of the following conditions: (1) The alicyclic transparent nylon includes one or more of PAMACM12, PAPACM12 and MACM12 / PACM12 copolymer; (2) The long carbon chain nylon includes one or more of PA1010, PA1012, PA1212 and PA12; (3) The relative viscosity of the alicyclic transparent nylon in concentrated sulfuric acid is 1.9 to 2.2; (4) The relative viscosity of the long carbon chain nylon in concentrated sulfuric acid is 2.2 to 2.4; (5) The mass ratio of the alicyclic transparent nylon to the long carbon chain nylon is (1-7): (3-4); (6) Based on the total mass of the alicyclic transparent nylon and the long carbon chain nylon, the amount of the additive added is 0.15wt%~3wt%.
5. The method for preparing the chemically resistant transparent polyamide according to any one of claims 1 to 2, characterized in that: The preparation method of the alicyclic transparent nylon comprises the following steps: The raw materials for preparing the alicyclic transparent nylon are mixed, and salt-forming reaction, prepolymerization reaction and polymerization reaction are carried out in sequence under closed conditions, and the alicyclic transparent nylon is obtained through extrusion, granulation and drying.
6. The method for preparing chemically resistant transparent polyamide according to claim 5, characterized in that: The preparation method of the alicyclic transparent nylon meets at least one of the following characteristics: (1) The raw materials for preparing the alicyclic transparent nylon include diamine monomers, diacid monomers, antioxidants and catalysts; (2) The salt-forming reaction is carried out under the protective atmosphere conditions of 140° C. to 150° C. and 0.1 MPa to 0.15 MPa; (3) The prepolymerization reaction is carried out at 270°C to 290°C and normal pressure, and the reaction time is 0.5h to 1h; (4) The polymerization reaction is carried out at 270°C to 290°C, a gas pressure of less than -0.08 MPa, and a reaction time of 10 min to 20 min.
7. The method for preparing a chemically resistant transparent polyamide according to any one of claims 1 to 2 and 6, characterized in that: The preparation method of the long carbon chain nylon comprises the following steps: The raw materials for preparing the long carbon chain nylon are mixed, and salt-forming reaction, prepolymerization reaction and polymerization reaction are carried out in sequence under closed conditions, and the long carbon chain nylon is obtained through extrusion, granulation and drying.
8. The method for preparing chemically resistant transparent polyamide according to claim 7, characterized in that: The preparation method of the long carbon chain nylon meets at least one of the following characteristics: (1) The raw materials for preparing the long carbon chain nylon include diamine monomer, diacid monomer, antioxidant and catalyst; (2) The salt-forming reaction is carried out under the protective atmosphere conditions of 90°C to 130°C and 0.1MPa to 0.15MPa; (3) The prepolymerization reaction is carried out at 220°C to 250°C and normal pressure, and the reaction time is 0.5h to 1h; (4) The polymerization reaction is carried out at 220°C to 250°C, a gas pressure of less than -0.08 MPa, and a reaction time of 10 min to 20 min.
9. A chemically resistant transparent polyamide, characterized in that: The chemical-resistant transparent polyamide is prepared by the preparation method of any one of claims 1 to 8.
10. A polyamide injection molded part, characterized in that: The invention comprises the chemically resistant transparent polyamide as claimed in claim 9.